International survey on Helicobacter pylori testing in patients with immune thrombocytopenia: Communication of the platelet immunology scientific and standardization committee. (6th January 2021) - Vishnu, Prakash; Duncan, Joanne; Connell, Nathan; Cooper, Nichola; Lim, Wendy; Rodeghiero, Francesco; Tomiyama, Yoshiaki; Grace, Rachael F.; Bakchoul, Tamam; Arnold, Donald M.; ,
Abstract : Essentials When to test and treat H pylori among patients with ITP is controversial. We report the results of an international survey administered to physicians with experience treating ITP across 39 countries. The decision to test for H pylori was influenced by country, country of origin, and concomitant gastrointestinal symptoms. Testing and treating for H pylori among patients with ITP varied across geographic regions. Abstract: Background: Investigations for patients suspected of immune thrombocytopenia (ITP) lack standardization. A controversial issue is whether such patients should be tested for Helicobacter pylori, a known cause of secondary ITP. Objectives: This Scientific and Standardization Committee Communication reports the results of an international survey to describe patterns of practice with respect to screening and treatment of H pylori among patients with ITP. Patients/Methods: A 17‐item scenario‐based questionnaire was delivered to hematologists in countries across the world. The questionnaire was pilot tested before use. We used snowball sampling and a contact list of physicians from the Platelet Disorders Support Association to identify survey respondents. Data were analyzed descriptively. Results: A total of 186 respondents from 39 countries completed the survey. Response rate from the snowball sample was 53.6%. Twenty‐nine percent (n = 55) of respondents always tested ITP patients for H pylori, and 53% (n = 98) sometimes tested. Of the 37 respondents from Asia and the Middle East, 51.4% (n = 19) always tested for H pylori for the stated reasons of high local prevalence and perceived benefit of treatment on platelet count levels. Respondents were more likely to test patients who were from Asia (145/177, 80%) and who had concomitant gastrointestinal symptoms (133/183, 72%). For eradication therapy, 71 of 118 (60.2%) respondents used the combination of a proton pump inhibitor, clarithromycin, and amoxicillin for 14 days. Conclusions: This international survey showed that testing for H pylori was most common in Asia and in patients from Asia. Testing and treating practices varied across geographic regions.